MiR-122 promotes metastasis of hepatoma cells by modulating RBM47-integrin alpha V-TGF-beta signaling - Lijun Mao; Hanru Yang; Ning Huang; Yao Li; Ye Sang; Chunxian Zeng (PLoS ONE, 2025)
MiR-122 is a liver-abundant miRNA, which is thought to harbor antitumorigenic activity. Elevated transforming growth factor-β (TGF-β) in hepatocellular carcinoma (HCC) microenvironment is a potent inducer for tumor metastasis. However, the involvement of miR-122 in regulation of TGF-β signaling and its implication in TGF-β-related HCC metastasis remains obscure. In this study, we demonstrated that miR-122 significantly enhanced the activities of the TGF-β pathway reporter, the levels of phosphorylation of Smad2 and Smad3, and the expression of mesenchymal markers (N-cadherin and vimentin) in HCC cells. Notably, miR-122 significantly promoted the migration and invasion in vitro and pulmonary metastasis of HCC cells in vivo. Mechanism investigations revealed that miR-122 directly suppressed the expression of RBM47, which was a novel RNA binding protein. RBM47 decreased the level of αv integrin (ITGAV) by promoting the degradation of mRNA via interacting with the AU-rich elements in its 3’UTR. Subsequently, the elevated ITGAV induced by miR-122 promoted activation of the latent TGF-β, thereby boosted the TGF-β signaling and then promoted cell motility. Taken together, miR-122 could promote metastasis of hepatoma cells by regulating RBM47-ITGAV-TGF-β signaling. These findings provide new insight into the regulatory network of miR-122, the complexity and robustness of TGF-β pathway and the mechanisms of HCC metastasis.